# How do you solve #3(x-1)=x#?

This is simple. Just proceed step by step.

Hence explained. Hope this helps.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve 3(x-1) = x, you would first distribute the 3 on the left side of the equation: 3 * x - 3 = x. Then, you would subtract x from both sides to isolate the x terms: 3x - x - 3 = 0. Simplify by combining like terms: 2x - 3 = 0. Finally, add 3 to both sides to isolate the x term: 2x = 3. Divide both sides by 2 to solve for x: x = 3/2 or 1.5.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7